Perceptions of Students and Faculty Regarding Problem Based Learning- Private and Public Sector Comparison - Zarmina Saga (Journal of Rawalpindi Medical College, 2017)
To study and compare the perception of students and faculty regarding problem based learning, in a public and a private sector medical college of Pakistan. Methods: In this mix method study in a private sector and a public sector medical college, in both these institutes, the curriculum for first year was divided into system based modules. Basic Sciences teaching was augmented by problem-based learning (PBL) in an integrated manner. Students were allocated randomly to batches, each comprising of 14-15 students. One facilitator was randomly allocated to each student’s batch. The response of students was evaluated based on structured questionnaires and their assessment was done by the faculty on structured evaluation forms. Results: Student’s response was categorized in four groups; quantitative analysis showed that majority of students from group A and B agreed that all members were involved as a team(62.6% & 57%), newly introduced PBL facilitated their learning process (64.9% and 61.8%), the learning environment was beneficial (55.3%. and 67.1%), and facilitator was helpful to complete the task given (78% and 64.54%).The facilitators rated the performances of the students based on a scoring system. The mean score of the students regarding their performances was 14.74 (SD+3.255) in group A and 10.64 (SD+4.55) - in group B; the maximum attainable scores being 20. The difference between their scores was statistically significant (P value <0.01). Conclusion: There is no difference in perception of students in a public and private medical college regarding PBL but there is statistically significant difference in performance of students, public sector students getting higher scores.